Upaya Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Kelas XI IPA 2 MAN 2 Pesisir Selatan Melalui Pelaksanaan Model Pembelajaran ROPES (Review, Overview, Presentation, Exercise, Summary) - Artita Salmi (Departement of Mathematics Education, 2022)
This research was motivated by the low activity of class XI IPA 2 MAN 2 Pesisir Selatan students during the mathematics teaching and learning process and the low learning outcomes obtained by class XI IPA 2 MAN 2 Pesisir Selatan students in learning mathematics. By using the ROPES learning model, it is able to improve students' active thinking skills during mathematics learning. Students do not only act as recipients of information provided by the teacher. They will try to find as much information as possible, then they can convey it through presentation activities. This research uses classroom action research. The purpose of the study was to describe efforts to improve the activities and learning outcomes of students in class XI IPA 2 MAN 2 Pesisir Selatan through the implementation of the Ropes learning model (Review, Overview, Presentation, Exercise, Summary). The action hypothesis is an increase in student learning activities in class XI IPA 2 MAN 2 Pesisir Selatan through the implementation of the ROPES learning model in mathematics subjects and an increase in student understanding and learning outcomes in class XI IPA 2 MAN 2 Pesisir Selatan through the implementation of the ROPES learning model in math subjects. This study consisted of two cycles, each of which consisted of four meetings. The percentage of completeness of cycle 1 is 68.75%. with an average of 75.84. The percentage of completeness in cycle 2 is 93.75%. with an average of 89.28. Student learning activities also showed a significant increase in each indicator.